Challenges in managing a transgender adolescent with attention-deficit/hyperactivity disorder and multiple psychiatric comorbidities: a case report - Lee, Eunsaem; Mathew, Namitha Maria; Narravula, Rithika; Dua, Sagar; Phagava, Tornike; Gultekin, Isa Emre; Oza, Mina; Parikh, Parinda (International Journal of Research in Medical Sciences, 2025)
Transgender and gender-diverse (TGD) adolescents are individuals whose experienced gender differs from their biological sex. This group is particularly vulnerable to psychiatric disorders due to both biological factors and psychosocial stressors. Common comorbidities include attention-deficit/hyperactivity disorder (ADHD), mood, and substance use disorders. To date, numerous studies have examined the association between transgender incongruence and ADHD. However, the links with other psychiatric conditions, such as bipolar disorder, remain unclear. A 19-year-old transgender male presented with emotional instability, episodic mood swings, impulsivity, and difficulties related to gender identity. He came out to his friends as male at the age of 13. He had previously been diagnosed with depression, anxiety, and ADHD at the age of 16. The patient also experienced recurrent hypomanic episodes characterized by grandiosity and decreased need for sleep, followed by depressive phases marked by self-injurious behavior and suicidal ideation. He had a history of childhood sexual trauma perpetrated by a friend. Adopted in infancy, his relationship with his family deteriorated after he disclosed his gender identity. He was started on a mood stabilizer and an antipsychotic, with the addition of stimulants considered for later management. This case underscores the clinical challenges of managing psychiatric comorbidities in TGD adolescents, particularly the intersection of ADHD and bipolar disorder. Emerging neurobiological and psychosocial evidence suggests potential shared pathophysiological mechanisms between TGD status and psychiatric comorbidities, although definitive causal pathways remain uncertain. Comprehensive care must integrate individualized pharmacological strategies with psychosocial interventions to address the multifaceted influences.